International Taxation and Luxembourg's Economy. (IMF Working Papers; Working Paper ;, 2020)
Luxembourg receives ample investment from multinational corporations, in part due to some attractive features in its international tax rules. Around 95 percent of these foreign investments pass through Luxembourg via companies performing holding and/or intra-group financing activities. While their contribution to Luxembourg's economy is modest relative to their large overall balance sheets, they still generate around 3 percent of GDP in tax revenue, create almost 4500 direct jobs, and spend almost 3 percent of GDP on salaries and purchases of business services. Ongoing changes in the international corporate tax framework pose risks to these economic contributions, which this paper attempts to quantify. It also discusses options for reforms in Luxembourg's tax system that could help offset adverse revenue and economic effects.